DAMPAK UMKM TERHADAP PENURUNAN PENJUALAN KFC DI INDONESIA - Rahman, Fadly (Taksasila Edukasi Insani, 2024)
This study aims to analyze the influence of Micro, Small and Medium Enterprises (MSMEs) on the decline in sales of fast food restaurants Kentucky Fried Chicken. MSMEs play an important role in the Indonesian economy, especially in helping to increase people's purchasing power with affordable prices and flavors that suit the tastes of the Indonesian people. This study uses a qualitative descriptive research method used to analyze topics and issues that rarely occur in MSMEs. The results of the study show that culinary MSMEs influence people's choices. The low price factor and easy-to-reach sales areas make consumers prefer MSME products to fast food restaurant products. The results of this study explain that MSMEs can compete with large companies.Keywords : MSMEs, business competition